2011
DOI: 10.1073/pnas.1113158108
|View full text |Cite
|
Sign up to set email alerts
|

Habit learning is associated with major shifts in frequencies of oscillatory activity and synchronized spike firing in striatum

Abstract: Rhythmic brain activity is thought to reflect, and to help organize, spike activity in populations of neurons during on-going behavior. We report that during learning, a major transition occurs in taskrelated oscillatory activity in the ventromedial striatum, a striatal region related to motivation-dependent learning. Early on as rats learned a T-maze task, bursts of 70-to 90-Hz high-γ activity were prominent during T-maze runs, but these gradually receded as bursts of 15-to 28-Hz β-band activity became pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
116
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 24 publications
8
116
1
Order By: Relevance
“…Numerous studies in mammals have shown that basal ganglia neurons change their task-related firing during learning (52,53), and that such changes can precede changes in cortical activity and behavior (54)(55)(56). Here, we extend these findings by directly demonstrating that the basal ganglia are required for specific, task-related cortical firing patterns that are critical for song motor plasticity.…”
Section: Discussionsupporting
confidence: 56%
“…Numerous studies in mammals have shown that basal ganglia neurons change their task-related firing during learning (52,53), and that such changes can precede changes in cortical activity and behavior (54)(55)(56). Here, we extend these findings by directly demonstrating that the basal ganglia are required for specific, task-related cortical firing patterns that are critical for song motor plasticity.…”
Section: Discussionsupporting
confidence: 56%
“…The relation between locomotion and BF gamma activity in the home cage is likely unrelated to the reported findings in the hippocampus and is probably a consequence of reduced gamma oscillations at very low movement-sensor levels that were not observed in the arena. Robust gamma oscillations have indeed been reported previously in the BF (31) as well as in nearby brain structures, notably including the VS, where other authors have observed gamma oscillations with a peak frequency around 50 Hz, similar to our study (62,64,(67)(68)(69)(70). However, VS 50-Hz gamma oscillation was observed during radial arm maze navigation (67,68) or rewarded decision making (63,64) and not during a "task-off," home-cage condition as in our study.…”
Section: Discussioncontrasting
confidence: 43%
“…Here we focused on the postperformance period, following up on studies of the rodent basal ganglia in which accentuated postperformance beta bursting was documented (15,26). Numerous studies in nonhuman primates have demonstrated significant task-related effects in the low beta band (4,5,(27)(28)(29), but except for the elegant studies of Tan and colleagues (30,31), oscillation during the postmovement period has not been analyzed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…
Studies of neural oscillations in the beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) have demonstrated modulations in beta-band power associated with sensory and motor events on time scales of 1 s or more, and have shown that these are exaggerated in Parkinson's disease. However, even early reports of beta activity noted extremely fleeting episodes of beta-band oscillation lasting <150 ms. Because the interpretation of possible functions for beta-band oscillations depends strongly on the time scale over which they occur, and because of these oscillations' potential importance in Parkinson's disease and related disorders, we analyzed in detail the distributions of duration and power for beta-band activity in a large dataset recorded in the striatum and motor-premotor cortex of macaque monkeys performing reaching tasks.
…”
mentioning
confidence: 99%
See 1 more Smart Citation